BANKS MEET IMMIGRANTS: A NEW ACTOR FOSTERING SOCIO-ECONOMIC INTEGRATION? - Daniela Nepote; Roberta Ricucci (European Regional Science Association (ERSA), 2010)
The percentage of immigrants in the total population of many European countries, including Italy, is rising. Despite being a structural component of society until now a substantial section of the banking market has shown considerable strategic uncertainty with regard to this question. The issue hinges on the limitation of the financial exclusion of immigrants, in other words, the inability to access necessary financial services in an appropriate form. The financial exclusion is of paramount importance as if it is not checked and resolved could be significantly damaging both in social and economic terms. In other words, banks can be considered as 'actors' involved in promoting the immigrants' socio-economic integration? Or, are they far away from the challenges of the immigration process? The paper will present an empirical analysis focused on the city of Turin (Italy) where the foreign citizens are 11% of the total population and aimed at knowing whether the Italian Retail Banking System have set out specific strategies for immigrants. The aim of the paper is twofold. Firstly, an investigation of the state of the art of the products on offer and the methods currently employed by retail banks. Secondly, an attempt to highlight the tools and development opportunities for innovatory operational methods is made. More precisely, in the paper, thanks to the collected data, an analysis of the offer of financial products for immigrants is presented. On the other hand, the paper will offer first data on the immigrants' economic behavior.
Keywords: 330; knowledge transfer; colleges of higher education; universities; SMEs